Extrato bruto de Vitex megapotamica apresenta efeito antinociceptivo e tipo-antidepressivo em ratos - Hamann, Fernanda Regina (2016)
Vitex megapotamica (Spreng) Moldenke is a native tree of South America, popularly known as Tarumã, has been used in folk medicine to treat inflammatory diseases. Although the effects of V megapotamica in animal models of inflammatory pain and depression have not been evaluated to date, a preliminary phytochemical analysis of leaves of V. megapotamica revealed the presence of flavonoid, compounds that exhibit anti-inflammatory and antidepressant-like effects described in literature, in addition to evidence that other plants of the same genus Vitex have analgesic effect dependent on the opioid system and mood modulation. This study investigated whether the crude leaf extract of V. megapotamica exhibit antinociceptive and antidepressant-like effects in models of chronic inflammation and depression induced by complete Freund's adjuvant (CFA). Chronic inflammation and like-depressive behavior were induced by intraplantar injection of CFA (100 ul/paw) in rats. The effect of oral crude extract of V. megapotamica (VmE; 3 30 mg/kg, p.o.) on nociception (thermal hyperalgesia, mechanical allodynia and arthritis score), inflammation (edema, myeloperoxidase activity), antidepressant-like (forced swimming test), locomotor activity (open field), gastrointestinal transit, hyperalgesia and naloxone-precipitated morphine withdrawal syndrome was evaluated. Naloxone (0.4 mg/kg, i.p.) was used to investigate the involvement of opioid system in the currently described effects of VmE. Crude extract caused antinociceptive/antidepressant-like effects in the CFA-induced chronic inflammation model, which was prevented by naloxone. The VmE extract (10 mg/kg, p.o.) did not alter locomotor activity, gastrointestinal function and inflammatory parameters and besides did not cause hyperalgesia. V. megapotamica induces opioid-dependent antinociception and antidepressant-like effect, without anti-inflammatory activity. The results support the use of VmE as a new analgesic and antidepressant.